Optimal design of air quality monitoring networks: A systematic review - Verghese, Sheelu; Nema, Arvind K. (Stochastic environmental research and risk assessment, 2022)
The optimal design of air quality monitoring network draws significant attention due to the severity associated with air pollution and constraints involved with the installation and maintenance of monitoring stations. Studies in this context, has evolved over time from statistical and geospatial design methods to heuristic and evolutionary techniques. In the past few decades multi objective, multi pollutant analysis has replaced consideration of single monitoring objective or placement of stations at pollution hot-spots. This comprehensive study provides a systematic literature review of the relevant conventional and contemporary approaches in this field based on a survey of 77 published works. This paper presents an overview of the design techniques applied by the studies in the last four decades and highlight major drawbacks and advantages. It concludes by identifying the knowledge gaps, the regional divide in the application of the modern techniques and its future scope.